CERITA RAKYAT SEBAGAI UPAYA PENGENALAN BAHASA DAN BUDAYA INDONESIA DALAM PEMBELAJARAN BIPA - Sindi Melinda; Helmi Muzaki (Jurnal Ilmiah SEMANTIKA, 2023)
Indonesian is the official language and the unity of the Indonesian nation. Currently, Indonesian is increasingly in demand by foreign speakers with various backgrounds. Foreign speakers learn not only Indonesian but also Indonesian culture. This study aims to describe folklore as an effort to introduce the Indonesian language and culture to foreign speakers. The method used in this research is library research. The results showed that folklore could be used as teaching material to introduce the Indonesian language and culture to foreign speakers. The use of folklore can also be integrated into the four language competencies: listening, reading, speaking, and writing.